Answer: r= 1.22
Step-by-step explanation:
Formula for amount with simple interest = ![P(1+rt)](https://tex.z-dn.net/?f=P%281%2Brt%29)
, where
P= principal value , r= rate of interest , t = time.
Given: P= $2000, t= 5 years, r= 1.25% = 0.0125
![A=2000(1+0.0125\times5)\\\\=2000(1.0625)=2125](https://tex.z-dn.net/?f=A%3D2000%281%2B0.0125%5Ctimes5%29%5C%5C%5C%5C%3D2000%281.0625%29%3D2125)
Formula to compute compound amount : ![P(1+r)^t](https://tex.z-dn.net/?f=P%281%2Br%29%5Et)
![=2000(1+r)^5](https://tex.z-dn.net/?f=%3D2000%281%2Br%29%5E5)
When both have same worth then
![2000(1+r)^5=2125\\\\\\ (1+r)^5=\dfrac{2125}{2000}\\\\\\ (1+r)^5=1.0625](https://tex.z-dn.net/?f=2000%281%2Br%29%5E5%3D2125%5C%5C%5C%5C%5C%5C%20%281%2Br%29%5E5%3D%5Cdfrac%7B2125%7D%7B2000%7D%5C%5C%5C%5C%5C%5C%20%281%2Br%29%5E5%3D1.0625)
taking log on both sides , we get
![5\ln (1+r)=\ln 1.0625\\\\\\ 5\ln (1+r)=0.0606246\\\\\\ \ln (1+r)=0.012125\\\\\\ 1+r=e^{0.005266}\\\\\\ 1+r=1.0122\\\\ r=0.0122\\\\ \\ r=1.22\%](https://tex.z-dn.net/?f=5%5Cln%20%281%2Br%29%3D%5Cln%201.0625%5C%5C%5C%5C%5C%5C%205%5Cln%20%281%2Br%29%3D0.0606246%5C%5C%5C%5C%5C%5C%20%5Cln%20%281%2Br%29%3D0.012125%5C%5C%5C%5C%5C%5C%201%2Br%3De%5E%7B0.005266%7D%5C%5C%5C%5C%5C%5C%201%2Br%3D1.0122%5C%5C%5C%5C%20r%3D0.0122%5C%5C%5C%5C%20%5C%5C%20r%3D1.22%5C%25)
Hence, Value of r= 1.22
A formula is recursive if it expresses the term
in terms of the previous one(s) ![a_{n-1},\ a_{n-2},\ \ldots,\ a_1](https://tex.z-dn.net/?f=%20a_%7Bn-1%7D%2C%5C%20a_%7Bn-2%7D%2C%5C%20%5Cldots%2C%5C%20a_1%20)
In this case, every term is 7 more than the previous one, so the formula for
will only involve
:
![a_n = a_{n-1} + 7](https://tex.z-dn.net/?f=%20a_n%20%3D%20a_%7Bn-1%7D%20%2B%207%20)
In fact, this formula is simply saying: for every index
, the term with that index is 7 more than the term before.
Also, we have to specify the starting point (otherwise we would go backwards indefinitely), so the complete recursive formula is
![a_n = a_{n-1} + 7,\quad a_1 = 2](https://tex.z-dn.net/?f=%20a_n%20%3D%20a_%7Bn-1%7D%20%2B%207%2C%5Cquad%20a_1%20%3D%202%20)
which means: start with 2 and generate every other term by adding 7 to the previous one.
Answer:
no
Step-by-step explanation:
the x value (-1) repeats therefore it ain't a function
Answer:
9/11
Step-by-step explanation:
Well we know there are 55 students in total and only 45 of them can either play a string or brass instrument.
So 45/55 is 9/11
Thus probably is 9/11 of a randomly selected student who plays either a string or brass.
Answer:
![4 \sqrt{6} \times \sqrt{3} = 12 \sqrt{2}](https://tex.z-dn.net/?f=4%20%5Csqrt%7B6%7D%20%20%5Ctimes%20%20%5Csqrt%7B3%7D%20%20%3D%2012%20%5Csqrt%7B2%7D%20)
Step-by-step explanation:
We want to simplify the radical expression:
![4 \sqrt{6} \times \sqrt{3}](https://tex.z-dn.net/?f=4%20%5Csqrt%7B6%7D%20%20%5Ctimes%20%20%5Csqrt%7B3%7D%20)
We write √6 as √(2*3).
This implies that:
![4 \sqrt{6} \times \sqrt{3} = 4 \sqrt{2 \times 3} \times \sqrt{3}](https://tex.z-dn.net/?f=4%20%5Csqrt%7B6%7D%20%20%5Ctimes%20%20%5Csqrt%7B3%7D%20%20%3D%204%20%5Csqrt%7B2%20%5Ctimes%203%7D%20%20%20%5Ctimes%20%20%5Csqrt%7B3%7D%20)
We now split the radical for √(2*3) to get:
![4 \sqrt{6} \times \sqrt{3} = 4 \sqrt{2} \times \sqrt{3} \times \sqrt{3}](https://tex.z-dn.net/?f=4%20%5Csqrt%7B6%7D%20%20%5Ctimes%20%20%5Csqrt%7B3%7D%20%20%3D%204%20%5Csqrt%7B2%7D%20%20%5Ctimes%20%20%5Csqrt%7B3%7D%20%20%5Ctimes%20%20%5Csqrt%7B3%7D%20)
We obtain a perfect square at the far right.
![4 \sqrt{6} \times \sqrt{3} = 4 \sqrt{2} \times (\sqrt{3} )^{2}](https://tex.z-dn.net/?f=4%20%5Csqrt%7B6%7D%20%20%5Ctimes%20%20%5Csqrt%7B3%7D%20%20%3D%204%20%5Csqrt%7B2%7D%20%20%5Ctimes%20%20%28%5Csqrt%7B3%7D%20%29%5E%7B2%7D%20)
This simplifies to
![4 \sqrt{6} \times \sqrt{3} = 4 \sqrt{2} \times 3](https://tex.z-dn.net/?f=4%20%5Csqrt%7B6%7D%20%20%5Ctimes%20%20%5Csqrt%7B3%7D%20%20%3D%204%20%5Csqrt%7B2%7D%20%20%5Ctimes%203)
This gives us:
![4 \sqrt{6} \times \sqrt{3} = 4 \times 3 \sqrt{2}](https://tex.z-dn.net/?f=4%20%5Csqrt%7B6%7D%20%20%5Ctimes%20%20%5Csqrt%7B3%7D%20%20%3D%204%20%5Ctimes%203%20%5Csqrt%7B2%7D%20)
and finally, we have:
![4 \sqrt{6} \times \sqrt{3} = 12 \sqrt{2}](https://tex.z-dn.net/?f=4%20%5Csqrt%7B6%7D%20%20%5Ctimes%20%20%5Csqrt%7B3%7D%20%20%3D%2012%20%5Csqrt%7B2%7D%20)